Insights Into the Controversial Aspects of Adiponectin in Cardiometabolic Disorders - Francischetti, Emilio Antonio; Dezonne, Rômulo Sperduto; Pereira, Cláudia Maria; de Moraes Martins, Cyro José; Celoria, Bruno Miguel Jorge; de Oliveira, Patrícia Aguiar Cardoso; de Abreu, Virgínia Genelhu (Hormone and Metabolic Research, 2020)
In 2016, the World Health Organization estimated that more than 1.9 billion adults were overweight or obese. This impressive number shows that weight excess is pandemic. Overweight and obesity are closely associated with a high risk of comorbidities, such as insulin resistance and its most important outcomes, including metabolic syndrome, type 2 diabetes mellitus, and cardiovascular disease. Adiponectin has emerged as a salutary adipocytokine, with insulin-sensitizing, anti-inflammatory, and cardiovascular protective properties. However, under metabolically unfavorable conditions, visceral adipose tissue-derived inflammatory cytokines might reduce the transcription of the adiponectin gene and consequently its circulating levels. Low circulating levels of adiponectin are negatively associated with various conditions, such as insulin resistance, type 2 diabetes mellitus, metabolic syndrome, and cardiovascular disease. In contrast, several recent clinical trials and meta-analyses have reported high circulating adiponectin levels positively associated with cardiovascular mortality and all-cause mortality. These results are biologically intriguing and counterintuitive, and came to be termed “the adiponectin paradox”. Adiponectin paradox is frequently associated with adiponectin resistance, a concept related with the downregulation of adiponectin receptors in insulin-resistant states. We review this contradiction between the apparent role of adiponectin as a health promoter and the recent evidence from Mendelian randomization studies indicating that circulating adiponectin levels are an unexpected predictor of increased morbidity and mortality rates in several clinical conditions. We also critically review the therapeutic perspective of synthetic peptide adiponectin receptors agonist that has been postulated as a promising alternative for the treatment of metabolic syndrome and type 2 diabetes mellitus.
Keywords: obesity; insulin resistance; adiponectin resistance; adiponectin paradox; diabetes mellitus